Prognostic Prediction for Recurrent/Residual CIN in HSIL Patients After Conization: An Updated Retrospective Study Based on Ambulatory Surgery - Huang G; Lin W; Gao H; Ren Y; Shen J; Xu S; Liu D; Cai Y; Lin C; Lin X; Jiang T; Dong B; et al. (Dove Medical Press, 2024)
Guanxiang Huang,1- 3,* Wenyu Lin,1- 3,* Hangjing Gao,1- 3 Yuan Ren,1- 3 Jun Shen,4 Shuxia Xu,5 Dabin Liu,6 Yuanjun Cai,6 Chengbin Lin,6 Xite Lin,1- 3 Tingting Jiang,1- 3 Binhua Dong,1- 3 Pengming Sun1- 3 1College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, Fuzhou, Fujian, 350001, People's Republic of China; 2Fujian Key Laboratory of Women and Children's Critical Diseases Research, Fujian Maternity and Child Health Hospital (Fujian Women and Children's Hospital), Fuzhou, Fujian, 350001, People's Republic of China; 3Fujian Clinical Research Center for Gynecological Oncology, Fujian Maternity and Child Health Hospital (Fujian Obstetrics and Gynecology Hospital), Fuzhou, Fujian, 350001, People's Republic of China; 4Fujian Provincial Cervical Disease Diagnosis and Treatment Health Center, Fujian Maternity and Child Health Hospital, Fuzhou, Fujian, 350001, People's Republic of China; 5Department of Pathology, Fujian Maternity and Child Health Hospital, Fuzhou, Fujian, 350001, People's Republic of China; 6Department of Gynecology, Fujian Maternity and Child Health Hospital, Fuzhou, Fujian, 350001, People's Republic of China*These authors contributed equally to this workCorrespondence: Pengming Sun; Binhua Dong, Laboratory of Gynecologic Oncology, Department of Gynecology, Fujian Maternity and Child Health Hospital, College of Clinical Medicine for Obstetrics & Gynecology and Pediatrics, Fujian Medical University, Fuzhou, Fujian, 350001, People's Republic of China, Tel +86-591-87558732 ; +86-13599071900, Fax +86-591-87551247, Email fmsun1975@fjmu.edu.cn, sunfemy@hotmail.com; dongbinhua86@fjmu.edu.cn, dbh18-jy@126.comBackground: There are currently few prognostic models for conization in patients with high-grade squamous intraepithelial lesion (HSIL) because it is a rapid procedure that typically collects less case information. The present study aimed to establish a rapid/accurate postoperative prognostic assessment model for these patients.Methods: This study included 631 nonpregnant participants with HSIL confirmed by histopathology from January 2015 to January 2018. The recurrent/residual cervical intraepithelial neoplasia (CIN) were divided into residual CIN, simple recurrent CIN and recurrent CIN accompanied with CIN progression. The recurrence/residual-free survival (RFS) time was defined as the time span from the time of surgery (baseline) until the first lesion of CIN was detected or the 1-/3-/5-year follow-up endpoint was reached.Results: After LASSO regression selection, the higher platelet-to-lymphocyte ratio (PLR) (OR = 1.006, p = 0.002), positive margin status (OR = 2.451, p = 0.021), HPV-16 (OR = 4.414, p < 0.001), − 18 (OR = 3.040, p = 0.009), − 56 (OR = 10.715, p=0.021), and non-HR-HPV (OR = 2.487, p = 0.028) infection showed significant difference in the Logistic model. And HPV-16 infection (OR = 6.159, p = 0.001) could promote recurrent CIN accompanied with CIN progression. In multivariate Cox regression models, the higher PLR (HR = 1.005/1.005/1.005, p = 0.020/0.002/0.003) and HPV-16 infection (HR = 2.758/2.836/2.674, p < 0.001) showed statistical difference during 1-/3-/5-year follow-up. While gland invasion (p = 0.081), margin status (p = 0.075) and HPV infection genotype (p = 0.150) did not showed statistical difference in multivariate Cox regression models based on LASSO regression. And gland invasion (p = 0.251/0.686) and HPV-58 infection (p = 0.148/0.813) also showed no statistical difference in optimized Logistic regression models.Conclusion: HPV-16, − 18, − 56 and non-HR-HPV infection status can be considered as indicators for recurrent CIN during the 5-year follow-up, especially for HPV-16 infection, which also lead to a CIN recurrence accompanied with disease progression. And the preoperative PLR level, gland invasion, positive margin may be predictors for recurrent/residual CIN during 1-, 3- and 5-year follow-up.Keywords: cervical intraepithelial neoplasia, higher platelet-to-lymphocyte ratio, human papillomavirus, conization, prognosis